Natural Killer T Cells (NKT cells) Functions in Malignancies - Balouchi-Anaraki, Sima; Nourozian, Marzie (Asian Pacific Journal of Cancer Biology, 2018)
CD1d-restricted natural killer (NKT) cells are unique innate like T lymphocyte that recognize glycolipid antigens. Two major NKT cell subsets, type I and type II, are different in their TCR repertoire and ligand specificity. Up on activation, NKT cells mediated strong and rapid responses through their ability to rapidly produce a large amount of both pro- and anti-inflammatory cytokines. Despite being a small population of αβ T lymphocytes, they can bridge the innate and adaptive arm of immune system through interaction with other immune components. These two subsets of NKT cells play critical apposite roles in anti-tumor immunity. This review focuses on the progress made in understanding the role of NKT cells in tumor immunity and how their activities can be useful in immunotherapeutic strategies.